Privacy preserving of intermediate dataset using hybridisation of oppositional gravitational search algorithm and elliptic curve cryptography. (21st June 2019) - Saravanan, S.; Venkatachalam, V.
Distributed computing gives the gigantic capacity ability to the clients to send their applications without any infrastructure investment. Based on the application lot of intermediate dataset will be created. To protecting these intermediate dataset is a challenging task. Moreover, encrypting all dataset is a time and cost consuming. To overcome the problem, in this paper we proposed a privacy preserving of intermediate dataset using a combination of oppositional gravitational search algorithm and elliptic curve cryptography (OGSA + ECC). Initially, we split the dataset into a number of the intermediate datasets, then, we choose the node corresponding intermediate dataset from the cloud using an oppositional gravitational search algorithm (OGSA). After that, we choose the sensitive data from the dataset using the information gain measure to minimise the processing time and cost. Then, using the ECC algorithm the sensitive data is encrypted and in the cloud the secure data are stored. The experimentation is carried out in terms of encryption time and memory use.